Gestión administrativa y productividad laboral de los trabajadores de la Municipalidad Distrital de Rosa Panduro - 2023 - Vásquez Mori, Romulo Javier (2023)
The general objective of this research was to determine the relationship between administrative management and labor productivity of the district municipality of Rosa Panduro-2023. The basic type, non-experimental design and descriptive level, the sample was made up of 28 collaborators from the district municipality of Rosa Panduro. The results showed through the Pearson correlation coefficient that its correlation value is 0.543 and significance is 0.003, which is less than 0.005, this indicates that there is a relationship between both variables. Concluding that the connection between administrative management and labor productivity of the municipality under study is positive, moderate and significant.